Microparticle and mitochondrial release during extended storage of different types of platelet concentrates. (3rd April 2017) - Marcoux, Geneviève; Duchez, Anne-Claire; Rousseau, Matthieu; Lévesque, Tania; Boudreau, Luc H.; Thibault, Louis; Boilard, Eric
Abstract: On activation, platelets release vesicles called microparticles (MPs). MPs are heterogeneous with regard to the presence or absence of mitochondria. We quantified MPs in platelet concentrates (PCs) taking their mitochondrial content into account. Platelet-rich plasma (PRP), buffy coat (BC) and apheresis (AP) PCs were tested through 7 days of storage. A combination of flow cytometry and spanning-tree progression analysis of density-normalized events (SPADE) was used to determine MP and mitochondrial release during storage. All the PC biochemical parameters complied with transfusion standards at all times. Platelet activation markers increased during storage and were higher for PRP than other types of PCs. Concentrations of MPs and extracellular mitochondria interpreted by SPADE algorithm were significantly higher in PRP than other in PCs and were stable throughout storage. The mode of preparation, rather than storage duration, impacts the release of MPs and mitochondria in PCs.